Adhesive capsulitis of the shoulder, its relationship to diabetes mellitus, and the need for effective treatment - Uddin, Md Taslim (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Abstract not available J Bangladesh Coll Phys Surg 2024; 42: 221-222